Pengaruh Beban Promosi terhadap Laba Operasional Bank Syariah Indonesia - Sukron, Jaenudin; Nani (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
Globalization has driven the spread of Islamic marketing internationally, with product standardization and global certification allowing companies to expand their reach. This creates innovative opportunities to meet a variety of consumer needs. Governments also play a significant role, with regulations supporting the development of the Islamic industry and monitoring business practices in accordance with Islamic principles. This phenomenon instills consumer confidence that the products they purchase meet strict Islamic ethical standards. In this context, Indonesia with the largest Muslim population has strived to become a global halal industry hub. Increasing consumer awareness of the halalness of products continues to grow, prompting countries to develop infrastructure and regulations, including strict halal certification. This study explores the impact of promotional costs on the operating profit of Bank Syariah Indonesia (BSI), highlighting the importance of a maximizing marketing strategy in a competitive environment. The findings indicate that promotional costs significantly affect operating profit, requiring BSI to optimize resource allocation in its marketing strategy. This study provides valuable insights for marketing management in the Islamic banking sector, as well as implications for the development of practice and theory in this area.